Geochemistry of fluid discharges from Peteroa volcano (Argentina-Chile) in 2010-2015: Insights into compositional changes related to the fluid source region(s) - Tassi, Franco (2016)
Fil: Tassi, Franco. Universita Degli Studi Di Firenze; Italia